Identification of recurrent FHL2-GLI2 oncogenic fusion in sclerosing stromal tumors of the ovary - Sarah H. Kim; Arnaud Da Cruz Paula; Thais Basili; Higinio Dopeso; Rui Bi; Fresia Pareja; Edaise M. da Silva; Rodrigo Gularte-Mérida; Zhen Sun; Sho Fujisawa; Caitlin G. Smith; Lorenzo Ferrando; et al. (Nature Communications, 2020)
Little is known about the genetics of sclerosing stromal tumor of the ovary, a rare type of sex cord-stromal tumor. Here, the authors use sequencing strategies to show that in a cohort of 26 tumor samples 65% carry a FHL2-GLI2 fusion gene and demonstrate in vitro that the fusion gene has oncogenic properties.